Nano- and Micromechanics of Crystalline Polymers - Galeski, Andrzej; Regnier, G (Nano- and Micro-Mechanics of Polymer Blends and Composites, 2009)
It is currently thought that crystalline polymers consists of lamellar crystals which areseparated from each other by a layer of amorphous polymer and are held together by tiemolecules through the amorphous phase [e.g. 1]. The lamellae are formed from mostly foldedchains. The thickness of lamellae is determined by the parameters such as interfacial energies,glass transition temperature and melting temperature, undercooling, segmental diffusivity, etc.The thickness reported lies usually in a narrow range between 3 and 20 nm as obtained fromobservations in various types of microscopes or calculated from the degree of crystallinity andlong period. It has been recognized that chain folding is not so regular as it was thought andmolecular packing in lamellae is subject to considerable and irregularly distributed disorderdepending on undercooling- regimes of crystallization. It has been demonstrated in variousways that the planar growth front will always break up into fibrous or cellular growth. Alsocrystallization of polymers leads to interface instability. More sophisticated treatment of theinstabilities involve perturbation analyses of planar interfaces, correlating diffusion,temperature gradients along the interface, and interfacial energy with the size of the growingcrystals.